A educação ambiental crítica e sua construção na escola pública: compreendendo contradições pelos caminhos da formação de professores - Souza, Daniele Cristina de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
In the Environmental Education (EE) public schools in Brazil vulnerable practices predominance, disconnected from the school curriculum and based in a conservationist and pragmatic of education perspective. Looking for help to evercome these limitations and considering the need for teacher training, being a way for these determinants are identified and understood, our main objetive was to understand a formative context in its in its contradictions, aiming at proposing theoretical and methodological elements favored the constructions of critical environmental school. The theoretical framework for understanding the movement of the real contradiction in its entirety was the historical and dialectical materialism. We focus on institutions, ideas, agents and supervisors rituals that must be viewed in the social totality. We sesk contributions in the Historical-Critical Pedagogy and reflect on the training of teachers and advocating a transformative praxis. The field research, a qualitative one, occured in the context of a project of the Programa Núcleo de Ensino UNESP - Bauru (SP), whose interventions occurred in two academic years. The first was a training education course, linked to an agency of the Secretary of Education of the State of São Paulo, aimed at problematization the official curriculum and of critical EE in shool. We collected data records written teacher's, of participant observation and notes in a field journal. We analyzed the curriculum official and documents on teacher education in the state. This phase brought in elements about interventions representatives of state control in teacher training and school practice, which is not conductive to overcoming its limitations as we aimed at ensuring the reproduction of the content and the form suggested by the policy linked to the official curriculum. We found consistency between the official curriculum ideas with regard to EE and to environmental issues and the concepts and...

Na Educação Ambiental (EA) presente nas escolas públicas no território nacional predominam práticas fragilizadas, desconectadas do currículo escolar e sustentadas em uma perspectiva de educação conservacionista e pragmática. Procurando contribuir para a superação destas limitações e considerando a necessidade de formação de professores, como um caminho para que os determinantes destas sejam identificados e compreendidos, nosso objetivo central foi compreender um contexto formativo em suas contradições, visando à proposição de elements teórico-metodológicos que favorecessem a construção da EA crítica na escola. Nosso referencial teórico para compreensão do movimento do real em sua totalidade e contradições foi o materialismo histórico-dialético. Focamos as instituições, as ideias, os agentes e os rituais pedagógicos visualizados na totalidade social. Buscamos aportes na Pedagogia Histórico-Crítica e refletimos sobre a formação de professores, defendendo a configuração de uma práxis transformadora. A pesquisa de campo, de cunho qualitativo, ocorreu no contexto de um projeto do Programa Núcleo de Ensino da UNESP - Bauru (SP), cujas intervenções ocorreram em dois anos letivos. A primeira fase se concretizou como um curso de formação continuada, vinculado a um órgão da Secretaria de Educação do Estado de São Paulo, visando à problematização do currículo oficiale da EA crítica da escola. Coletamos dados pelos registros escritos dos professores, na observação participante e anotações em diário de campo. Analisamos o currículo oficial e os documentos sobre a formação de professores do estado. Esta fase nos trouxe elementos representantes das intervenções de controle do Estado na formação dos professores e nas práticas escolares, o que não favorece a superação de suas limitações, pois estão voltadas para garantir a reprodução do conteúdo, da forma sugerida pela política...
Keywords: Educação ambiental; Curriculos - São Paulo; Ensino fundamental; Pratica de ensino; Environmental education